Assessing cognitive and metacognitive strategies during algebra problem solving among university students - Bayat, Sahar; Ahmad Tarmizi, Rohani (Elsevier, 2010)
One of the most important goals of mathematics learning is to enhance mathematical knowledge, which includes mathematical concepts and skills in problem solving. Thus, efforts to achieve these goals have increased. The purpose of this study was to assess the cognitive strategies and Algebra problems solving performance among university students. The design adopted for this study was a descriptive correlation design. The subjects of this study were selected from First Year mathematics students who took Algebra course in a public university in Malaysia. The Cognitive Strategy Questionnaire, which comprised of 18 items, was used to assess the student's specific cognitive strategy for solving the given Algebra problems. Algebra problem solving performance was measured using a test which included routine and non-routine problems, based on the topics covered in the course. The results showed that there is no significant correlation between Algebra problem solving performance with shallow cognition strategy (r = -.134, p > 0.05). Similarly, there is no significant relationship between the student's performance with deep cognitive strategy (r = .124, p > 0.05). Results also showed that there is significant and strong relationship between student's Algebra problem solving performance and overall performance in the course (r = .721, p < 0.05). Findings also revealed that there was positive and moderate significant correlation between overall meta-cognitive strategies and performance of Algebra problem solving (r = 0.394, p < 0.05). In addition, there was a significant positive and moderate relationship between overall meta-cognitive strategies with overall performance in the course (r = .390, p < 0.05). Specifically, there is significant relationship between overall performance in the course and all three subscales of meta-cognition (knowledge, planning and evaluation). In conclusion, meta-cognitive strategies may have impact on mathematical performance among university students whilst cognitive strategies indicated minimal impact.